DETERMINAN PEMILIHAN ALAT KONTRASEPSI TRADISIONAL DI WILAYAH PERKOTAAN DAN PERDESAAN PROVINSI BALI - Indrayathi, Putu Ayu; Marfianti, Istiana; Damadita, Putu Dwiki; Listiani, Ni Made Ari; Swandewi, Luh Kadek Ratih (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 2 (2021): Agustus 2021DO - 10.24843/ACH.2021.v08.i02.p01, 2021)
ABSTRACT The result of 2017 Indonesian Health Demographic Survey (SDKI 2017) shows the number of traditional contraception uses in Bali Province has increased from 7% in 2012 to 13% in 2017. The use of traditional contraception methods in Bali is double that of national figures. The purpose of this study is to determine the factors associated with the choice of traditional contraception methods in urban and rural areas of married women in Bali Province. This study is a secondary data analysis from the 2017 SDKI. The sample size is 357 women ages 15-49 years. There are 22 independent variables that are studied, and the dependent variable is the use of traditional contraception methods. The results of multivariate analysis showed that significantly related factors are uppermiddle category wealth quintile (p = 0.027, OR = 11.16, 95% CI = 1.31-94.54), top category wealth quintile (p = 0.049, OR = 9.04, 95% Ci = 1.01-80.77), obtained family planning information from the pharmacist (p = 0.034, OR = 2.1, 95% CI = 1.05-4.17), side effects of contraception (p = 0.002, OR = 2.95, 95% CI = 1.48-5.88), decision making to use contraception with partner (p = 0.029, OR = 2.43, 95% CI = 1.09-5 , 43), and decision-makers using family planning only husband/partner (p = 0.015, OR = 4.24, 95% CI = 1.32-13.56). The variables that become protective factor is the newspaper reading variables (p = 0.008, OR = 0.42, 95% CI = 0.23-0.79). The conclusion that can be drawn from this study is the use of traditional contraception methods in married women in Bali Province influenced by wealth quintiles, habits of reading the newspaper, obtaining contraception information from pharmacists, side effects of using contraception and those who make decisions about using contraception.   Keywords : Contraception method, Traditional contraception, Balinesse married women.     ABSTRAK Hasil Survei Demografi Kesehatan Indonesia (SDKI) 2017 menunjukkan angka penggunaan KB tradisional di Provinsi Bali mengalami peningkatan dari 7% pada 2012 menjadi 13% pada 2017. Penggunaan alat/cara KB tradisional di Bali dua kali lipat lebih banyak dibandingkan angka nasional. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan pemilihan alat/cara KB tradisional di daerah perkotaan dan perdesaan pada wanita kawin di Provinsi Bali. Penelitian ini merupakan analisis data sekunder dari data SDKI 2017. Besar sampel adalah 357 wanita usia subur (WUS) dengan usia 15-49 tahun. Terdapat 22 variabel bebas yang diteliti, sedangkan variabel terikatnya adalah penggunaan alat/cara KB tradisional. Hasil analisis multivariat menggunakan analisis regresi logistik menunjukan bahwa faktor -faktor yang berhubungan secara signifikan terhadap pemilihan alat kontrasepsi tradisional adalah kuintil kekayaan kategori menengah atas (p=0,027, OR=11,16, 95% CI=1,31-94,54), kuintil kekayaan kategori teratas (p=0,049, OR=9,04, 95% Ci=1,01-80,77), mendapatkan informasi KB dari apoteker (p=0,034, OR=2,1, 95% CI=1,05-4,17), efek samping penggunaan kontrasepsi (p=0,002, OR=2,95, 95% CI=1,48-5,88), mengambil keputusan menggunakan KB bersama pasangan (p=0,029, OR=2,43, 95% CI=1,09-5,43)), dan pengambil keputusan menggunakan KB hanya suami/pasangan (p=0,015, OR=4,24, 95% CI=1,32-13,56). Variabel yang menjadi faktor protektif adalah variabel membaca koran (p=0,008, OR=0,42, 95% CI=0,23-0,79). Simpulan yang dapat ditarik dari penelitian ini adalah penggunaan alat/cara KB tradisional pada wanita kawin di Provinsi Bali dipengaruhi oleh kuintil kekayaan, kebiasan membaca koran, mendapatkan informasi KB dari apoteker, efek samping penggunaan kontrasepsi dan pihak yang mengambil keputusan dalam menggunakan KB.   Kata kunci : Penggunaan alat/cara KB, KB tradisional, WUS di Bali.